β-blocker therapy and cardiac events among patients with newly diagnosed coronary heart disease - Andersson, Charlotte; Shilane, David; Go, Alan S; Chang, Tara I; Kazi, Dhruv; Solomon, Matthew D; Boothroyd, Derek B; Hlatky, Mark A (Journal of the American College of Cardiology, 2014)
The effectiveness of beta-blockers for preventing cardiac events has been questioned for patients who have coronary heart disease (CHD) without a prior myocardial infarction (MI). The purpose of this study was to assess the association of beta-blockers with outcomes among patients with new-onset CHD. We studied consecutive patients discharged after the first CHD event (acute coronary syndrome or coronary revascularization) between 2000 and 2008 in an integrated healthcare delivery system who did not use beta-blockers in the year before entry. We used time-varying Cox regression models to determine the hazard ratio (HR) associated with beta-blocker treatment and used treatment-by-covariate interaction tests (p(int)) to determine whether the association differed for patients with or without a recent MI. A total of 26,793 patients were included, 19,843 of whom initiated beta-blocker treatment within 7 days of discharge from their initial CHD event. Over an average of 3.7 years of follow-up, 6,968 patients had an MI or died. Use of beta-blockers was associated with an adjusted HR for mortality of 0.90 (95% confidence limits [CL]: 0.84 to 0.96), and an adjusted HR for death or MI of 0.92 (CL: 0.87 to 0.97). The association between beta-blockers and outcomes differed significantly between patients with and without a recent MI (HR for death: 0.85 vs. 1.02, p(int) = 0.007; and HR for death or MI: 0.87 vs. 1.03, p(int) = 0.005). Use of beta-blockers among patients with new-onset CHD was associated with a lower risk of cardiac events only among patients with a recent MI.